2017
DOI: 10.21010/ajtcam.v15i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Anticancer Activities of Extracts From Urginea Maritima Fruits

Abstract: Background: Increasing antibiotic resistance among human pathogenic microorganisms and the failure of conventional cancer therapies attracting great attention among scientists in the field of herbal medicine to develop natural antimicrobial and anticancer drugs. Thus, the antimicrobial and anticancer activities from fruits of the medicinal plant Urginea maritima (L.) Baker that unexplored previously were investigated in this study. Materials and Methods: Fruits of U. maritima plant were collected, dried, groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In the current study, the anticancer potential of a novel medicinal plant common in Mediterranean regions, namely D. maritima was investigated. D. maritima has long been used for the management and treatment of many pathological conditions [ 10 , 11 , 12 , 13 , 14 ]. In cancer settings, several preceding in vitro studies have reported potent anticancerous and selective cytotoxic effects of D. maritima on different cancer types, including breast, lung, lymphoma, and prostate cancer [ 10 , 11 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, the anticancer potential of a novel medicinal plant common in Mediterranean regions, namely D. maritima was investigated. D. maritima has long been used for the management and treatment of many pathological conditions [ 10 , 11 , 12 , 13 , 14 ]. In cancer settings, several preceding in vitro studies have reported potent anticancerous and selective cytotoxic effects of D. maritima on different cancer types, including breast, lung, lymphoma, and prostate cancer [ 10 , 11 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…D. maritima has long been used for the management and treatment of many pathological conditions [ 10 , 11 , 12 , 13 , 14 ]. In cancer settings, several preceding in vitro studies have reported potent anticancerous and selective cytotoxic effects of D. maritima on different cancer types, including breast, lung, lymphoma, and prostate cancer [ 10 , 11 , 13 , 15 ]. However, [ 16 ] the cytotoxic effect of D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pharmacological developments have been made in the staging and treatment of lung cancer over decades, further research on medicinal plants is needed to ascertain early prevention of lung cancers. An abundant number of evidence suggests that increased consumption of fruits and vegetables is a relatively easy and practical strategy to reduce significantly the incidence of cancer (Obeidat and Sharab, 2018). Artocarpus heterophyllus belongs to the family Moraceae, It is also reported for a rich source of phytochemicals which embraces various enzyme that is been used in growth supplementation (Ali et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers had shown that methanol and acetone extracts of the bulbs of U. sanguinea had appropriate antibacterial activity against Gram-negative bacteria, especially P. aeruginosa, while the extracts showed no considerable antiparasitic properties (9). The research showed that fruit extracts of U. maritima exhibited antimicrobial and anticancer activities (10).…”
Section: Introductionmentioning
confidence: 99%